Practices of (neoliberal) governmentality: racial and gendered gaze in Jhumpa Lahiri’s fiction - Asl, Moussa Pourya; Nurul Farhana Low Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Michel Foucault’s notion of neoliberal governmentality is important in the context of the portrayal of the private sphere of the family by diasporic writers. Family, which is generally defined in terms of its functionality, when considering the difficulties of integration into the non-natal culture from the perspective of the uprooted migrants, is often referred to, erroneously, as the locus of privacy, individuality and autonomy. Among the works of the contemporary writers of Indian diaspora experience in America, Jhumpa Lahiri’s Interpreter of Maladies (1999) has addressed issues of displacement, assimilation and acculturation modifying Indian diaspora individuals and families. This essay analyses two of her short stories “Mrs. Sen’s” and “When Mr. Pirzada Came to Dine” to examine the strategies employed to monitor, regulate and (re)form racial and gendered identities within the seemingly private domain of the Indian diaspora families in the process of establishing a socially acceptable congruence of images for the members of the migrant family. Using the personal sphere of the family as an example of constraint that perpetually fixes subjects to their disciplinary apparatuses, Lahiri portrays the capillary functioning of it through various acts of looking. This essay seeks to explore some of the complex dynamics of the gaze in Lahiri’s stories with a particular focus on the coercive character of power and the unequal gendering of the (examining) gaze.